Carcinoma Buccal Mucosa Underlying a Giant Cutaneous Horn: A Case Report and Review of the Literature - Sunil Kumar; Priyank Bijalwan; Sunil K. Saini (Case Reports in Oncological Medicine)
Cutaneous horn is a conical, dense, and hyperkeratotic protrusion that often appears similar to the horn of an animal. Giant cutaneous horns are rare; no incidence or prevalence has been reported. The significance of cutaneous horns is that they occur in association with, or as a response to, a wide variety of underlying benign, premalignant, and malignant cutaneous diseases. A case of giant cutaneous horn of left oral commissure along with carcinoma left buccal mucosa is reported here as an extremely rare oral/perioral pathology.